2017
DOI: 10.1038/cmi.2017.5
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid receptor promotes the function of myeloid-derived suppressor cells by suppressing HIF1α-dependent glycolysis

Abstract: Immunomodulatory signaling imposes tight regulations on metabolic programs within immune cells and consequentially determines immune response outcomes. Although the glucocorticoid receptor (GR) has been recently implicated in regulating the function of myeloid-derived suppressor cells (MDSCs), whether the dysregulation of GR in MDSCs is involved in immune-mediated hepatic diseases and how GR regulates the function of MDSCs in such a context remains unknown. Here, we revealed the dysregulation of GR expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 48 publications
(66 reference statements)
1
52
0
Order By: Relevance
“…SIRT1‐HIF‐1α axis plays an important role in regulating cellular metabolism. In our research, we found that SIRT1‐HIF‐1α axis is associated with the differentiation of several types of immune cells, including Th9 and MDSCs. Our team research showed that SIRT1 can deregulate function and differentiation of MDSCs through orchestrating HIF‐1α‐dependent glycolysis .…”
Section: Main Functional Characteristics Of Mdscsmentioning
confidence: 64%
“…SIRT1‐HIF‐1α axis plays an important role in regulating cellular metabolism. In our research, we found that SIRT1‐HIF‐1α axis is associated with the differentiation of several types of immune cells, including Th9 and MDSCs. Our team research showed that SIRT1 can deregulate function and differentiation of MDSCs through orchestrating HIF‐1α‐dependent glycolysis .…”
Section: Main Functional Characteristics Of Mdscsmentioning
confidence: 64%
“…For instance, glucocorticoids which are used routinely as firstline treatment and regulate transcription of many metabolic genes [91] associated with glycolytic, autophagy and mTOR pathways [92,93]. For instance, glucocorticoids which are used routinely as firstline treatment and regulate transcription of many metabolic genes [91] associated with glycolytic, autophagy and mTOR pathways [92,93].…”
Section: Targeting Metabolism In Rheumatoid Arthritismentioning
confidence: 99%
“…As highlighted above, studies examining metabolic pathways in RA have identified specific pathways, enzymes or metabolic intermediates that could potentially be targeted; however, many of our current treatment strategies are already known to alter metabolic pathways. For instance, glucocorticoids which are used routinely as firstline treatment and regulate transcription of many metabolic genes [91] associated with glycolytic, autophagy and mTOR pathways [92,93]. Conventional disease-modifying antirheumatic drugs (DMARDs) for RA and psoriatic arthritis (PsA), including methotrexate, leflunomide and apremilast, are anti-metabolic, where they target purine or pyrimidine nucleotide metabolism, the effects of which are known to inhibit both T cells and synovial fibroblast proliferation.…”
Section: Targeting Metabolism In Rheumatoid Arthritismentioning
confidence: 99%
“…Glucocorticoids have revolutionized the treatment of patients with arthritis and other inflammatory diseases since the mid‐20th century . They bind to the glucocorticoid receptor and regulate transcription of genes involved in metabolism . The efficacy of glucocorticoids has been linked to inhibition of glycolysis , while the stimulation of autophagy and mTOR activity are mechanisms that have been identified as underlying the resistance to glucocorticoids.…”
Section: Metabolic Targets Of Treatment In Rheumatic Diseasesmentioning
confidence: 99%